Empire and power in the reign of Suleyman narrating the sixteenth-century Ottoman world - Sahin, Kaya (Cambridge studies in Islamic civilization, 2015)
On a torrid August day in 2009, I visited Celalzade Mustafa's final resting place in Istanbul's Eyup district, in a neighborhood called Nisanca. The chancellor (nisanci) is buried in the cemetery adjoining the small mosque built for him by Sinan, the chief imperial architect. The mansion where Mustafa composed his works, welcomed fellow literati, and provided advice to young and aspiring secretaries is long gone, probably destroyed in the fire of 1780, if not before.